Does chronic use of caffeine reduce its acute ergogenic effects during high intensity interval training? - Salam, H.; Hopker, J.; Marcora, S. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Based on extensive research showing positive effects on performance (Spriet, 2014), many athletes use caffeine before and during competitions (Coso et al, 2011). However, the use of caffeine during training is not well understood. Therefore, the first aim of this study was to test the hypothesis that caffeine acutely increases power output, heart rate (HR), and blood lactate during high intensity interval training (HIIT). The second aim was to test the hypothesis that chronic use of caffeine reduce its hypothesised acute ergogenic effects during HIIT (tolerance). Methods: Twenty recreational male endurance athletes (age 33±9 years; VO2max 55.3 ±8.9 ml/kg/min) took part in the study. Each participant completed 7 test visits in the laboratory. During the first was an incremental test, and familiarized. A second familiarization occurred during visit 2. During visit 3 and 4, the acute ergogenic effects of caffeine (3 mg/kg body weight) ingested 1 hour before HIIT were assessed using a placebo-controlled. HIIT consisted of 4 bouts (RPE 16, 17, 18, and 19) of 4 min each. Participants were randomly allocated toptwo groups. One group took caffeine 3 times a week 1 hour before 3 of their regular training sessions. The other group took placebo (Dextrose). After 4 weeks of such chronic supplementation, all participants performed a follow-up assessment of VO2max (visit 5) and the acute effects of caffeine (visits 6 and 7). Relevant main effects and interactions on VO2max and power output/HR/blood lactate during HIIT were analysed by mixed analyses of variance (ANOVA). Results: No significant changes in VO2max were observed in either groups after 4 weeks of training. As hypothesised, caffeine acutely increased power output, HR and blood lactate during HIIT at both the baseline and follow-up assessments. There were no significant interactions and main effects of time suggesting the development of tolerance to these acute ergogenic effects of caffeine during HIIT after 4 weeks of chronic supplementation. Discussion: Caffeine ingestion one hour prior to HIIT acutely increases power output, HR and blood lactate for the same RPE. Frequent use of caffeine before training (3 times a week for 4 weeks) does not reduce these acute ergogenic effects of caffeine during HIIT. This observation argues against the development of tolerance and suggests that pre-training caffeine ingestion is a useful strategy to increase training intensity. Whether this increase in training intensity leads to greater gains in performance needs to be investigated in future studies with more controlled training programs and longer follow up periods.